Abnormal psychology - Beltran, Jane Q. (Manila, Philippines : Rex Book Store, 2008)
This book aims to give the students a comprehensive background of the different maladjustment and mental disorders, their causes, symptoms, and possible prevention and treatment.
Module I Abnormal behavior and nature -- Module II Psychological factors and physical illness -- Module III The neurosis -- Module IV Personality disorders, addictive disorders, sexual dysfunction and variants -- Module V Affective disorders, schizophrenia, and paranoia -- Module VI Organic mental disorder, mental retardation, behavior disorders of childhood and adolescence.
Includes bibliographical references and index.
Keywords: ABNORMAL PSYCHOLOGY